A Comparison of Leg Muscle Oxygenation, Cardiorespiratory Responses, and Blood Lactate between Walking and Running at the Same Speed - Alexandros Stathopoulos; Anatoli Petridou; Nikolaos Kantouris; Vassilis Mougios (MDPI AG, 2024)
It is not known whether different gait modes, or movement patterns, at the same speed elicit differences in muscle oxygen oxygenation, expressed as muscle oxygen saturation (SmO2). Thus, the aim of this study was to compare the oxygenation of two leg muscles (vastus lateralis and gastrocnemius medialis), as well as the heart rate, respiratory gases, and blood lactate between two gait modes (walking and running) of the same speed and duration. Ten men walked and ran for 30 min each at 7 km/h in a random, counterbalanced order. SmO2, heart rate, and respiratory gases were monitored continuously. Blood lactate was measured at rest, at the end of each exercise, and after 15 min of recovery. Data were analyzed by two-way (gait mode × time) or three-way (gait mode × muscle × time) ANOVA, as applicable. Heart rate and oxygen consumption were higher when running compared to walking. SmO2 was lower during exercise compared to rest and recovery, in gastrocnemius medialis compared to vastus lateralis, and in running compared to walking. Blood lactate increased during exercise but did not differ between gait modes. In conclusion, running caused higher deoxygenation in leg muscles (accompanied by higher whole-body oxygen uptake and heart rate) than walking at the same speed (one that was comfortable for both gait modes), thus pointing to a higher internal load despite equal external load. Thus, preferring running over walking at the same speed causes higher local muscle deoxygenation, which may be beneficial in inducing favorable training adaptations.